Implementasi Mandat Konstitusional Putusan MK Nomor 91/PUU-XVIII/2020 dalam Dinamika Hubungan MK dengan Pembentuk Undang-Undang - Halmadiningrat, I Made; Hafidz, Violla Reininda (Kertha Patrika; Vol 45 No 3 (2023), 2023)
The discrepancy between Constitutional Court Decision Number 91/PUU-XVII/2020 on the review of the Job Creation Law and the PERPPU on Job Creation has created constitutional incompatibilities. The research aims to analyze the executorial power in the final and recall nature of the Constitutional Court's decision on the follow-up of the Constitutional Court's decision by the legislators and (ii) the implementation of the constitutional mandate of Constitutional Court Decision Number 91/PUU-XVIII/2020 on Job Creation in the Job Creation PERPPU in the dynamics of the relationship between the Constitutional Court and the legislators. This research uses a combination of normative-doctrinal methods using a contextual approach, legislative approach, conceptual approach and case approach. The results of this study indicate that the Constitutional Court's decision has executorial power over the final and binding nature erga omnes. The Constitutional Court's conditional unconstitutional decision regarding the formal examination of the Job Creation Law has shifted the role of the Constitutional Court as a positive legislature which also results in the nature of the Constitutional Court's decision as a quasi-law. Follow-up of the Constitutional Court's decision is also considered important as compliance with the constitution. This research also shows that there is a mismatch between the constitutional mandate in Constitutional Court Decision Number 91/PUU-XVII/2020 and the follow-up carried out by the President as one of the branches of lawmaking power. This mismatch is clearly a form of constitutional delegitimization and straddles the final and binding Constitutional Court decision.